Analysis of dust dispersion in the loading of a bulk carrier ship using CFD and DEM. (3rd April 2022) - Roberts, Jon; Andrews, Liam; Wypych, Peter
Abstract: Dust generation and dispersion continue to be a major concern for many in the industries that rely on bulk materials handling, and the ability to predict dust generation and dispersion remains challenging. This study looks at the use of computational fluid dynamics (CFD) and discrete element method (DEM) as a means of predicting dust generation and dispersion. The paper outlines work completed on predicting dust dispersion during the loading process of a bulk carrier using the Rotabox™ system for a stevedoring company at a port in Australia. CFD simulations are conducted to analyze the induced air flow generated inside the cargo hold of a bulk carrier including typical cross-wind conditions. Coupled CFD-DEM simulations are conducted to analysis the air flow inside the cargo hold driven by the unloading of the bulk material. Dust particle free-settling time is used to assess the dust cloud formation and dispersion based on the flow conditions predicted by CFD-DEM simulations. The study finds that the unloading process is likely to disperse dust into the cargo hold at a level that without dust suppression would result in dust being dispersed into the broader environment by the typical cross-wind conditions at the port.